Can metal nanoparticles be a threat to microbial decomposers of plant litter in streams? - Pradhan, Arunava (2011)
The extensive use of nanometal-based products increases the chance of their release into aquatic environments, raising the question whether they can pose a risk to aquatic biota and the associated ecological processes. Aquatic microbes, namely fungi and bacteria, play a key role in forested streams by decomposing plant litter from terrestrial vegetation. Here, we investigated the effects of nanocopper oxide and nanosilver on leaf litter decomposition by aquatic microbes, and the results were compared with the impacts of their ionic precursors. Alder leaves were immersed in a stream of Northwest Portugal to allow microbial colonization before being exposed in microcosms to increased nominal concentrations of nanometals (CuO, 100, 200 and 500 ppm; Ag, 100 and 300 ppm) and ionic metals (Cu2+ in CuCl2, 10, 20 and 30 ppm; Ag+ in AgNO3, 5 and 20 ppm) for 21 days. Results showed that rates of leaf decomposition decreased with exposure to nano- and ionic metals. Nano- and ionic metals inhibited bacterial biomass (from 68.6% to 96.5% of control) more than fungal biomass (from 28.5% to 82.9% of control). The exposure to increased concentrations of nano- and ionic metals decreased fungal sporulation rates from 91.0% to 99.4%. These effects were accompanied by shifts in the structure of fungal and bacterial communities based on DNA fingerprints and fungal spore morphology. The impacts of metal nanoparticles on leaf decomposition by aquatic microbes were less pronounced compared to their ionic forms, despite metal ions were applied at one order of magnitude lower concentrations. Overall, results indicate that the increased release of nanometals to the environment may affect aquatic microbial communities with impacts on organic matter decomposition in streams.